EPILEPSY DISEASE AND ITS MODERN SOLUTION. - The hump Fatima Sharipovna NAZAROVA; The Teachers Of Halilova Sevinch. (Scholar Express Journals, 2024)
In recent years, developing countries in sugar diabed, cancer, heart-blood vessels, base-action diseases of a wide spread. These injuries among especially, epilepsy, i.e. the possible wide spread. This of the disease, age and gender does not choose. It all young and men and women equally common can. Oksford university professor, psychological scientists Charles Newton it as follows described: “Epilepsy so sick, the brain than the more neuron and electronic network out of, as a result, people in normal is a scan, feeling and even hushi the loss of cases is observed. It is from parents to children to be passed can. Other hereditary causes are there. Infection, when born , obtained trauma, head injury , and even stroke and brain cancer is also a disease the cause is”. This disease types a lot of be, tutqanog'i have people who are in the death condition is also common is. The disease with bouts who has the patient in time-time cognitive ability reduced, their deeds office, reach , unable to will remain.
Keywords: epilepsy; disease; trauma